The Sweet Spot: Continued Search for the Glycemic Threshold for Macrovascular Disease—A Retrospective Single Center Experience. (14th October 2012) - Boguszewski, Andrzej; Teklinski, Andrew; Rosman, Howard; Desai, Devang; Ali, Sajid; Szpunar, Susan; Moore, Ruth; Maciejko, James
Abstract : Background . Atherosclerotic cardiovascular disease (ASCVD) is a common complication of diabetes mellitus and impaired fasting glucose (IFG). We hypothesized that the relation of fasting glucose levels to ASCVD is linear, with the prevalence of clinical ASCVD beginning to increase even among individuals currently categorized as normoglycemic. Methods . Patient charts were retrospectively reviewed from our Dyslipidemic Preventive Cardiology Clinic. We evaluated the prevalence of ASCVD relative to fasting glucose levels in a cross-section of patients at high risk for ASCVD. Results . In 558 dyslipidemic patients, ASCVD prevalence increased with increasing fasting glucose levels. A significantly higher prevalence of ASCVD was observed among patients with fasting glucose levels between 90 and 99 mg/dL versus lower levels. As glucose levels increased from 90 to 125 mg/dL, the prevalence of ASCVD continued to rise in parallel. Logistic regression analysis with forward likelihood ratio stepwise selection indicated that individuals with fasting blood glucose of 90–99 mg/dL were 2.6 times more likely to have ASCVD than those with lower levels of fasting blood glucose. Conclusion . Our findings suggest that the current cutoff for impaired fasting glucose of 100 mg/dL may be somewhat conservative and that a level above 90 mg/dL may be more appropriate as an ASCVD risk factor, particularly in patients with a lipid disorder.